Analysis of Secondary Effects and Bond Behavior due Prestressing - Halvonik, Jaroslav; Pažma, Peter; Laco, Ján (Advanced Materials Research, 2015)
Subject of this article is an introduction of experimental research realized by department of a concrete structures and bridges at Slovak University of Technology in Bratislava. This research was focused on analysis of secondary effects due prestressing by changing statically indeterminate system to a kinematical mechanism. Other part of this research was observing of bond behaviour of a strands coated with corrosion protection agents.